Nicely semiramified division algebras over Henselian fields - Karim Mounirh (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the structure of nicely semiramified valued division algebras. We prove that any defectless finite-dimensional central division algebra over a Henselian field E with an inertial maximal subfield and a totally ramified maximal subfield (not necessarily of radical type) (resp., split by inertial and totally ramified field extensions of E) is nicely semiramified.